Pineal cyst-related sleep disorders – a narrative review - Gałązka, Jakub Krzysztof; Domagalski, Łukasz; Hoffman, Zofia; Homa, Piotr; Kaleta, Natalia; Drabczyńska, Katarzyna; Czyżewski, Wojciech (Journal of Education, Health and Sport, 2023)
The pineal gland is an endocrine gland, which is responsible for the human circadian rhythm, through the regulation of its hormone – melatonin. The most common pathology of a pineal gland is pineal cyst – its population incidence is estimated as 1-23%, depending on the publication. The most common symptoms of a pineal cyst include headache (87%), visual field defects (54%), nausea/vomiting (34%), and dizziness/vertigo (31%). Among the majority of patients with the asymptomatic pineal cyst, the wait-and-see strategy is proper. According to the newest meta-analyze, the prevalence of sleep disturbances among patients with pineal cyst estimates to be 17%. The results of direct melatonin level measurements in pineal cysts remain unclear. The study focused on sleep disturbances in pediatric patients with pineal cysts and showed a significantly higher score on Sleep Disturbance Scale for Children (SDSC) in the domains of disorders of excessive sleepiness and disorders of initiating and maintaining sleep than the control groups. The impact of lesion on sleep quality correlated with its size. The pineal cyst may be considered a rare, and potentially reversible, cause of sleep disorders. Nevertheless, according to the present reports (often opposite to each other), this thesis and the mechanism of its occurrence need to be further researched.